ChemInform Abstract: Electrochemical Synthesis of p‐Type Zn‐Doped α‐Fe2O3 Nanotube Arrays for Photoelectrochemical Water Splitting. Issue 34 (1st August 2013) - Qi, Xiaopeng; She, Guangwei; Wang, Meng; Mu, Lixuan; Shi, Wensheng
Abstract The title nanotube arrays are prepared on transparent conductive substrates by anodic electrodeposition using ZnO nanorod arrays as sacrificial template and Zn source, and aqueous FeCl2 solution as the electrolyte (75 °C, pH 4.0).